IMPROVING STUDENT COGNITIVE ABILITY THROUGH CONTEXTUAL LEARNING MODEL IN THE CLASS II LEARNING SCHOOL OF BASIC SCHOOL - Suhartini, Ai Tintin; Murni, Sukma (IKIP Siliwangi, 2018)
The development and characteristics of students in primary school age vary between students in the low class and high class. The learning process in the lower class of elementary schools has not been able to develop their cognitive skills in full, in contrast to the characteristics of students in the high class. In the classroom action research activities carried out in class II SD Negeri Sosial 1 Cimahi Elementary School this aims to improve the cognitive abilities of students through the application of contextual learning models. The use of contextual learning models applied refers to Jean Piaget's cognitive theory. The method used in this study is the Class Action Research method. The research sample was students of class IIB in SD Negeri Sosial 1 Cimahi City. The design of this study is through the stages of the learning cycle to find the final results of the study. The results of the study prove that the contextual learning model is suitable for learning in low-grade elementary schools.